Experiences of Gender-Based Violence at a South African University: Prevalence and Effect on Rape Myth Acceptance - Finchilescu, Gillian (Journal of interpersonal violence, 2021)
Instances of gender-based violence (GBV) on university campuses are rarely reported to the authorities. This makes it difficult to gauge the prevalence of this problem, which in turn affects efforts for prevention. This article describes a university-wide online survey aimed at assessing, first, the prevalence of GBV experienced by the three sectors in the community—students, academic and research staff, and professional/administrative staff. Many of the findings concurred with research elsewhere—students were the predominant victims of GBV; men were the main perpetrators; and instances of rape occurred mainly when the victim/survivor was under the influence of alcohol or drugs. In contrast to some of the more well-known U.S. surveys (e.g., Georgetown University), we found relatively few instances of students being exploited by staff members. Occurrences of contrapower harassment were also reported in our survey. The second aim investigated whether rape myth acceptance was related to experiences of GBV. We found that women who had these experiences were more rejecting of rape myths than women who had not had such experiences. The opposite was found for White men. White men who had experienced GBV were more accepting of the rape myths than those who had not had such experiences. It was suggested that this reflected a need for these male victims to establish their hegemonic masculine identity. In general, the level of rape myth acceptance was relatively low. This suggested that widespread victim-blame, and self-blame does not account for the low levels of GBV reports to officials. A limitation of the study was the relatively low response rate (1,350 respondents), which was likely caused by the student protests over university fees that were ongoing at the time of the survey. These protests caused considerable disturbance for all sectors of the university community.